2017
DOI: 10.1002/2017gl075020
|View full text |Cite
|
Sign up to set email alerts
|

What Happens Before a Southward IMF Turning Reaches the Magnetopause?

Abstract: Previous observations have shown a ∼10–15 min time delay in the ionospheric response to solar wind directional discontinuities marked by either southward or northward interplanetary magnetic field (IMF) turnings. We have studied one southward IMF turning observed by Time History of Events and Macroscale Interactions during Substorms (THEMIS) and GOES in the dayside magnetosphere. Using a global MHD model, we have reproduced the magnetopause motion in this event. We find that the observed delay in the ground re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 42 publications
6
19
0
Order By: Relevance
“…Samsonov et al () recently used an MHD simulation to study a DD accompanied by a southward turning and showed that the DD propagation time through the magnetosheath was 14 min in good agreement with the ground response seen in changes of the Polar Cap North (PCN) index (Troshichev et al, ). Samsonov et al () noted a significant deceleration of the DD as it approached the magnetopause. The IMF was northward before the DD, and a magnetic barrier (Pudovkin, ) formed near the magnetopause.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Samsonov et al () recently used an MHD simulation to study a DD accompanied by a southward turning and showed that the DD propagation time through the magnetosheath was 14 min in good agreement with the ground response seen in changes of the Polar Cap North (PCN) index (Troshichev et al, ). Samsonov et al () noted a significant deceleration of the DD as it approached the magnetopause. The IMF was northward before the DD, and a magnetic barrier (Pudovkin, ) formed near the magnetopause.…”
Section: Introductionmentioning
confidence: 79%
“…Finally, it takes only about 1 min from the contact of the DD with the subsolar magnetopause to the first ground (ionospheric) response. During the same event, Samsonov et al () noted a sunward motion of the subsolar magnetopause for ∼10 min before the DD had reached the magnetopause. Their MHD simulation showed that the dissipation of the magnetic barrier caused by magnetosheath reconnection gradually decreases the total pressures applied to the magnetopause thus resulting in the sunward magnetopause motion.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Assuming the nose of the bow shock at 14 R E , we get the propagation time from THC to the bow shock about 6 minutes. The propagation time through the magnetosheath can be estimated as 14 min (Samsonov et al, 2017). Thus, the southward turning of IMF Bz could reach the magnetopause 20 min after registration onboard THC, and the ionospheric convection is expected to respond in ~ 20 min after that (Hairson and Heelis, 1995).…”
Section: Pre-onset Phenomena In the Interplanetary Spacementioning
confidence: 99%